Dyadic Death Homicide Suicide Case Report - Gürses, Murat Serdar; Eren, Bülent; Akan, Okan; Cantürk, Nergis; Çetin, Selçuk (The Bulletin of Legal Medicine, 2014)
Homicide-suicide event is defined as killing him or herself right after or in a short time period after killing one or more people. As events involve a couple, the term dyadic death is also used. Dyadic death events are generally observed to occur in families and in addition to this perpetrators are men, victims are women. Among the reasons of dyadic death are corruption in family relationships, somatic or mental diseases and financial problems. Marzuk et al. initially reported that homicide-suicide events are classified depending on perpetrator-victim relationship and perpetrator’s motive (jealousy, revenge, financial issues.. etc). Dyadic death event of the couple who divorced approximately 30 years ago and lived together for one last year again, in this homicide-suicide event victim died with incisive-perforating instrument and on the other hand the perpetrator died by hanging himself was discussed in the literature.Keywords: Homicide-suicide; dyadic death; incisive-perforating instrument wound; hanging.
Keywords: homicide-suicide; dyadic death; incisive-perforating instrument wound; hanging